2018
DOI: 10.1039/c8nr05450a
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature wafer-scale synthesis of two-dimensional SnS2

Abstract: Research on two-dimensional (2D) metal dichalcogenides is rapidly expanding owing to their unique characteristics that do not exist in bulk materials. The industrially compatible development of these emerging materials is indispensable to facilitate the transition of 2D metal dichalcogenides from the research stage to the practical industrial application stage. However, an industrially relevant method, i.e., the low-temperature synthesis of wafer-scale, continuous, and orientation-controlled 2D metal dichalcog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 36 publications
1
30
0
Order By: Relevance
“…Each layer corresponds to a (040) plane 31 of SnS for an interspacing of 2.8 Å and a (001) plane of SnS 2 for an interspacing of 5.9 Å. 4 The transformed SnS layers are observed not only near the surface but also at the interface with the SiO 2 substrate despite insufficient cycles for transformation. The transformed SnS is even observed below the SnS 2 that had not yet transformed.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Each layer corresponds to a (040) plane 31 of SnS for an interspacing of 2.8 Å and a (001) plane of SnS 2 for an interspacing of 5.9 Å. 4 The transformed SnS layers are observed not only near the surface but also at the interface with the SiO 2 substrate despite insufficient cycles for transformation. The transformed SnS is even observed below the SnS 2 that had not yet transformed.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This allows the formation of MoO 3 /MoS 2 heterostructures when oxidizing few-layer MoS 2 crystals. Similarly, two-step growth of 3 nm SnS 2 crystals is achieved by sulfurization of ALD-grown tin oxides (SnO and SnO 2 ) on Al 2 O 3 substrate . Two-step growth of 2D perovskites has also been reported by many groups. Ha et al reported the synthesis of 2D perovskite nanoplatelets from 2D PbI 2 .…”
Section: Synthesismentioning
confidence: 93%
“…In this work, atomic layer deposition (ALD) is employed for the growth of MoS 2 films. Although chemical vapor deposition (CVD) is still the preferred synthesizing technique to achieve the best quality 2D TMDCs in large areas, ,, in the quest of Ångstrøm level thickness control and highly conformal layers (suitable for 3D structures) while maintaining a low thermal budget, required for industry processes, ALD has also been gaining attention in recent years. We comprehensively study the impact of device processing conditions on the chemistry involved at the metal-to-MoS 2 interface and connect the two to the current–voltage ( I – V ) results, obtained from electrically characterizing the fabricated FETs, with ALD-based MoS 2 films and Ti/Au contacts. In pursuit of optimizing the contacts to our MoS 2 , we investigate the influence of thermal annealing and plasma cleaning the contacts (with O 2 and Ar) on the overall device electrical performance while scaling down the Ti interlayer thickness.…”
Section: Introductionmentioning
confidence: 99%